Winning ugly : NATO's war to save Kosovo - Daalder, Ivo H. (Brookings Institution Press, 2000)
"In this first in-depth study of the Kosovo crisis, Ivo Daalder and Michael O'Hanlon answer these and other questions about the causes, conduct, and consequences of the war. Based on interviews with many of the key participants, they conclude that notwithstanding important diplomatic mistakes before the conflict, it would have been difficult to avoid the Kosovo war. That being the case, U.S. and NATO conduct of the war left much to be desired. For more than four weeks, the Serbs succeeded where NATO failed, forcefully changing Kosovo's ethnic balance by driving 1.5 million Albanians from their homes and more than 800,000 from the country. Had they chosen to massacre more of their victims, NATO would have been powerless to stop them." "In the end, NATO won the war by increasing the scope and intensity of bombing, making serious plans for a ground invasion, and moving diplomacy into full gear in order to convince Belgrade that this was a war Serbia would never win." "The Kosovo crisis is a cautionary tale for those who believe force can be used easily and in limited increments to stop genocide, mass killing, and the forceful expulsion of entire populations. Daalder and O'Hanlon conclude that the crisis holds important diplomatic and military lessons that must be learned so that others in the future might avoid the mistakes that were made in this case."--Jacket